O Pai-Nosso na teologia de Leonardo Boff e na perspectiva cultural moçambicana - Matsovele, Anastâncio Jemo (2015)
This dissertation is a result of research and analysis of the subjects around the The Lord´s Prayer . It has the purpose of confronting the content within the prayer with the lives of the mozambican people in its relations to God and others. Having as a start point the essay of Leonardo Boff s The Lord´s Prayer: The Prayer of Integral Liberation (1979). Deriving from this, the theme of the dissertation is centered on The Lord´s Prayer according to the theology of Leonardo Boff and on mozambican cultural perspective. It presents a brief exegetic study of the Lord´s Prayer. It develops a discussion around the Lord´s Prayer according to the theology of Leonardo Boff. It follows with the exposure of some compelling arguments that this prayer, to the mozambican people, is not a theory, but life itself. It acknowledges God as the father; the respect for His holy Name; recognition of His Kingdom´s supremacy; recognition of the superiority of His will; the breaking of bread which makes communion; forgiveness that heals grief and the trust in God in times of temptation and for the future itself. The conclusion brings a comparative synopsis of the Lord´s Prayer in the theological and cultural mozambican perspective.